Haiti : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2008)
The paper provides an assessment of poverty and inequality on the basis of the data gathered from the most recent surveys. The vision of state and nonstate actors as well as the challenges to be met by 2015 was outlined; the paper also summarizes the major areas of work decided upon by the government of Haiti. Macroeconomic framework and policies are also discussed. Finally, this study covers financing, implementation, and monitoring of the poverty reduction strategy. The growth strategy is based on four key areas or growth vectors.